SOME RESULTS OF FOREST ECOSYSTEM SERVICES MODEL ON THE TERRITORY OF YUNDOLA AND TETEVEN (Innovation in Woodworking Industry and Engineering design, 2026)
Some results, obtained by the work of international research project: Integrated future-oriented management of forest landscapes - INTEGRAL are presented. The decision support system (DSS) SYBILA were partly adapted and used for the first time in Bulgaria. The results of indicators changes model: total volume of standing timber, volume and yield class structure of possible timber cutting volume and total biomass volume under different forest management regimes on the territory of Yundola and Teteven for the period of 50 years are analysed.